(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
Theoretical and analytical material on the problems of professional theoretical and practical training of bachelors in the field of physical education for preschoolers and ways to solve them. Preschool education is designed for bachelors, masters and many specialists of educational institutions.